Microbial diversity and fermentation optimization of tempoyak from Durian and Durian Lai - MARWATI MARWATI; KRISHNA PURNAWAN CANDRA; ASWITA EMMAWATI; MIFTAKHUR ROHMAH (Society for Indonesian Biodiversity, 2025)
Abstract. Marwati, Candra KP, Emmawati A, Rohmah M. 2025. Microbial diversity and fermentation optimization of tempoyak from Durian and Durian Lai. Biodiversitas 26: 4908-4922. Tempoyak, a traditional fermented durian product, is a rich source of probiotic lactic acid bacteria (LAB) with potential as a functional food. This study aimed to optimize the fermentation conditions of tempoyak made from Durian Lai (Durio zibethinus × Durio kutejensis, DZ_K) using Response Surface Methodology-Box Behnken Design (RSM-BBD) and to compare its bacterial community structure with that of regular durian tempoyak (DZ). The effects of salt (2-4%), sugar (0.5-1.5%), and fermentation time (2-4 days) on LAB counts, pH, acidity, sugar, and moisture content were evaluated, and optimal conditions for DZ_K were identified as 2.46% salt, 1.01% sugar, and 2 days of fermentation, yielding log 9.5 CFU/g LAB, pH 5.56, and acceptable acidity and sugar levels. Microbial profiling using 16S rRNA gene sequencing (Illumina MiSeq) revealed distinct bacterial communities, with DZ_K dominated by Pediococcus (56.5%) and Weissella (12.23%), while DZ exhibited greater diversity, including Leuconostoc (42.43%) and Acetobacter (8.78%). Alpha diversity indices indicated higher microbial richness in DZ, and ordination analyses confirmed a clear separation between the two fermentation types. These findings suggest that DZ fermentation supports broader microbial diversity, potentially enhancing flavor complexity and fermentation stability, whereas DZ_K fermentation favors a LAB-driven process, improving product stability and probiotic potential, thereby providing a scientific basis for optimizing tempoyak production to enhance microbiological quality and safety.